1-Allyl-4-phenyl-2,3-dihydro-1H-1,5-benzodiazepin-2-one - Ballo, D.; Ahabchane, N.H.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The seven-membered ring in the title compound, C(18)H(16)N(2)O, adopts a boat conformation with the two phenylene carbons representing the stern and the methylene C atom the prow. The dihedral angle between the best plane through the seven-membered ring and the phenyl ring is 62.13 (3)degrees.